Body mass index classification misses subjects with increased cardiometabolic risk factors related to elevated adiposity - Gómez-Ambrosi, J; Silva, C; Galofré, J C; Escalada, J; Santos, S; Millán, D; Vila, N; Ibañez, P; Gil, M J; Valentí, V; Rotellar, F; Ramírez, B; et al. (International Journal of Obesity, 2012)
Context: Body mass index (BMI) is widely used as a measure of overweight and obesity, but underestimates the prevalence of both conditions, defined as an excess of body fat. Objective: We assessed the degree of misclassification on the diagnosis of obesity using BMI as compared with direct body fat percentage (BF%) determination and compared the cardiovascular and metabolic risk of non-obese and obese BMI-classified subjects with similar BF%. Design: We performed a cross-sectional study. Subjects: A total of 6123 (924 lean, 1637 overweight and 3562 obese classified according to BMI) Caucasian subjects (69% females), aged 18–80 years. Methods: BMI, BF% determined by air displacement plethysmography and well-established blood markers of insulin sensitivity, lipid profile and cardiovascular risk were measured. Results: We found that 29% of subjects classified as lean and 80% of individuals classified as overweight according to BMI had a BF% within the obesity range. Importantly, the levels of cardiometabolic risk factors, such as C-reactive protein, were higher in lean and overweight BMI-classified subjects with BF% within the obesity range (men 4.3±9.2, women 4.9±19.5 mg l −1 ) as well as in obese BMI-classified individuals (men 4.2±5.5, women 5.1±13.2 mg l −1 ) compared with lean volunteers with normal body fat amounts (men 0.9±0.5, women 2.1±2.6 mg l −1 ; P <0.001 for both genders). Conclusion: Given the elevated concentrations of cardiometabolic risk factors reported herein in non-obese individuals according to BMI but obese based on body fat, the inclusion of body composition measurements together with morbidity evaluation in the routine medical practice both for the diagnosis and the decision-making for instauration of the most appropriate treatment of obesity is desirable.